Relações intersemióticas entre literatura, cinema, artes plásticas e desenho em dois romances de Márcio Souza - Luís Heleno Montoril del Castilo (Universidade de Brasília, 2013)
This paper aims to explore the relationships between different artistic forms – li- terature, cinema, plastic arts and design – investigating the operation of the bond- ing techniques (originating end of the plastic arts) and assembly (film technique) and how they were implemented in literature. To this end, we as an object of analysis the novels of the writer amazon Márcio Souza Galvez imperador do Acre (1983) and A resistível ascensão do Boto Tucuxi ([1977] 1982).